Comparative study of the polyphenol content-related anti-inflammatory and antioxidant activities of two Urera aurantiaca specimens from different geographical areas - Carla Marrassini; Ignacio Peralta; Claudia Anesini (BMC, 2018)
Abstract Background Urera aurantiaca is an Argentinean species that has been traditionally used to treat symptoms of inflammation. The aim of this study was to determine and compare the anti-inflammatory and antioxidant effects of two specimens of Urera aurantiaca obtained in the provinces of Salta and Misiones, which are two different geographical areas of Argentina. Methods The anti-inflammatory activity of the extracts was tested in LPS-stimulated macrophages through the DPPH radical scavenging activity, the SOD-like activity, the reducing power and the inhibition of lipid peroxidation. The anti-inflammatory activity was also evaluated by the inhibition of albumin denaturation and proteinase inhibitory action tests. The total polyphenols, flavonoids and tannins content were quantified. Results Both extracts were able to reduce the augmented NO release in LPS-activated macrophages and showed antioxidant and in vitro anti-inflammatory activities. The polyphenols content was higher in the extract obtained from the specimen from Salta than in that obtained in Misiones. This finding accounts for the higher anti-inflammatory and antioxidant properties obtained with the former. Conclusion The differences in chemical composition and the biological activities observed between the extracts are probably related to the different environmental conditions found in both provinces.